Production and characterization of electrospun fish sarcoplasmic protein based nanofibers - Sahin, Yesim M.; Su, Sena; Ozbek, Burak; Yucel, Sevil; Pinar, Orkun; Kazan, Dilek; Oktar, Faik N.; Ekren, Nazmi; Gunduz, Oguzhan (ELSEVIER SCI LTD, 2018)
In this study, poly (e-caprolactone) (PCL) and fish sarcoplasmic protein (FSP) (Mw < 200 kDa) composite nanofibers were fabricated by electrospinning technique. Solution properties such as density, viscosity, conductivity and surface tension were studied as a function of FSP content in the solution. The morphology, molecular interaction, degradation as well as thermal and tensile properties of PCL/FSP nanofibers were investigated. The results show that smooth and beadless PCL/FSP nanofibers with the diameters ranging from 120 +/- 29 nm to 139 +/- 41 nm were obtained. The average diameters decreased and the diameter distributions narrowed with the addition of optimum FSP amount. The characteristic picks of FSP and PCL were identified in the composite nanofibers by structural analyses. PCL/FSP nanofibers exhibited high degradation ability in comparison to electrospun pure PCL nancifibers. Moreover, the PCL/FSP nanofibers exhibit good mechanical properties (tensile strength of 5.55 MPa) with the additional FSP content. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Composite nanofibers; Electrospinning technique; Fish sarcoplasmic protein; Nanomaterials; Polycaprolactone; Tensile strength; FABRICATION; DIAMETER; GELATIN; FIBERS; PARAMETERS; MORPHOLOGY; SCAFFOLDS; POLYMER; Engineering; Food Science & Technology